Evaluation of a chest radiograph reading and recording system for tuberculosis in a HIV-positive cohort. Issue 6 (June 2017) - Kosack, C.S.; Spijker, S.; Halton, J.; Bonnet, M.; Nicholas, S.; Chetcuti, K.; Mesic, A.; Brant, W.E.; Joekes, E.; Andronikou, S.
Abstract : Aim: To assess the impact of introducing a chest radiograph reading and recording system (CRRS) with a short training session, on the accuracy and inter-reader variability of tuberculosis (TB) interpretation of chest radiographs (CXRs) by a group of non-expert readers in a human immunodeficiency virus (HIV)-positive cohort. Materials and methods: A set of 139 CXRs was reviewed by a group of eight physicians pre- and post-intervention at two clinics in Shan State, Myanmar, providing HIV/TB diagnosis and treatment services. The results were compared against the consensus of expert radiologists for accuracy. Results: Overall accuracy was similar pre- and post-intervention for most physicians with an average area under the receiver operating characteristic curve difference of 0.02 (95% confidence interval: –0.03, 0.07). The overall agreement among physicians was poor pre- and post-intervention (Fleiss κ= 0.35 and κ= 0.29 respectively). The assessment of agreement for specific disease patterns associated with active TB in HIV-infected patients showed that for intrinsically subtle findings, the agreement was generally poor but better for the more intrinsically obvious disease patterns: pleural effusion (Cohen's kappa range = 0.37–0.67) and milliary nodular pattern (Cohen's kappa range = 0.25–0.52). Conclusion: This study demonstrated limited impact of the introduction of a CRRS on CXR accuracy and agreement amongst non-expert readers. The role in which CXRs are used for TB diagnosis in a HIV-positive cohort in similar clinical contexts should be reviewed. Highlights: Diagnosis of TB using CRRS in non-radiologist physicians. Interpretation accuracy for tuberculosis did not increase using a CRRS. Focus should be given to easily recognizable disease patterns. Chest x-ray interpretation is a complex and challenging task.